IFIP International Federation for Information Processing
DOI: 10.1007/978-0-387-39229-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for IT Governance Assessment and Design

Abstract: Abstract. IT Governance has become an increasingly important process in delivering business value from IT. A number of IT governance frameworks have been proposed as the MIT -CISR framework and COBIT. However, there is no proposal of a systematic methodology for IT Governance assessment and design, considering the possibility of joint usage of multiple frameworks. This paper presents a systematic methodology for IT governance assessment and design, specified through different phases, their activities and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…To define a methodology for the development and implementation of an ICT Governance mechanism, it is necessary to make a survey based on the organization needs, which can be conducted through information gathering techniques [40]. In the implementation of the pilot, we conducted the activities through these four techniques: survey, brainstormings, focus group and semi-structured interviews.…”
Section: Proposal Of a Methodology For The Implementation Of Ict Procmentioning
confidence: 99%
“…To define a methodology for the development and implementation of an ICT Governance mechanism, it is necessary to make a survey based on the organization needs, which can be conducted through information gathering techniques [40]. In the implementation of the pilot, we conducted the activities through these four techniques: survey, brainstormings, focus group and semi-structured interviews.…”
Section: Proposal Of a Methodology For The Implementation Of Ict Procmentioning
confidence: 99%
“…It has been reported that they make up about 75% of the operating budget and represents approximately 4% of gross revenue". In some countries, for instance organisations in North America and Western Europe, have increased investment in IT and focused on ensuring that IT delivers value around 4.2% of the annual revenues (Clementi et al, 2006). In general, worldwide IT spending reached $3.4 trillion in 2010 with 4.6 percent increase from 2009 (Norshidah Mohamed, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As "metas de desempenho do negócio" determinam a eficácia esperada das estratégias da companhia e permitem avaliar o sucesso dos esforços de governança. As métricas e responsabilidades de TI definem a contribuição de TI para as metas de desempenho da empresa e permitem avaliar a eficácia de TI de maneira separada (CLEMENTI; CARVALHO, 2006).…”
Section: Itilunclassified